Avoiding oxygen induced Pb vacancies for high thermoelectric performance of n-type Bi-doped Pb1-xBixTe compounds. (October 2022) - Wang, C.; Liu, K.; Tao, Q.; Zhao, X.; Ning, S.; Tang, Y.; Chen, Z.; Wu, J.; Su, X.; Uher, C.; Zhang, Q.; Tang, X.
Abstract: For n -type PbTe based compounds with relatively low optimal concentration (10 19  cm −3 ), the accompanied structural defects play pivotal role on the charge transport upon doping with alien valent atoms. Herein, we report that Oxygen has huge influence on the defect evolution and thermoelectric properties in n -type PbTe for the first time. A boosted thermoelectric figure of merit ZT of ∼1.12 at 673 K and a ZT ave of 0.84 in the range of 300–873 K are achieved for vacuum sintered Bi-doped PbTe with the powders ground under the protection of Ar. This is in sharp contrast with the same Bi-doped PbTe material sintered with the powders ground in the air, which reaches a ZT ave of 0.52. This distinct thermoelectric properties in Bi-doped PbTe compounds are strongly correlated to Bi dopant, the vacancy defects ( V P b ″ and V T e ⋅ ⋅ ) induced during the fracturing process, and oxygen in the air. The coexistence of Bi dopant and oxygen lowers the formation energy of Pb vacancies and induces large number of O–Bi related Pb vacancies in the structure, yielding an acceptor-like effect. Such negatively charged Pb vacancies in the structure exert a strong long-range coulombic repulsion force on the electrons, leading to a low doping efficiency, a low carrier mobility (200 cm 2  V −1  s −1 ), and inferior electronic properties. Whereas, the protection provided by Ar effectively avoids the contamination by oxygen and prevents the formation of O–Bi related Pb vacancies, which appears remarkably effective in enhancing the electronic transport. A high carrier mobility of 1300 cm 2  V −1  s −1 is attained in slightly doped Pb0·9995 Bi0·0005 Te sample and this contributes to an ultra-high power factor of 40 μW cm −1  K −2 for the Pb0·9995 Bi0·0005 Te sample at room temperature. The high PF ave exceeds 25 μW cm −1  K −2 in the range of 300–723 K. The work provides a new insight into the formation mechanism of structural defects and a new avenue for suppressing the cation vacancies, resulting in higher performance of n -type PbTe-based compounds. Graphical abstract: Image 1 Highlights: We firstly report that Oxygen has huge influence on the defect evolution and thermoelectric properties in n -type PbTe. The oxygen-related acceptor effect and its reaction equation have been proposed in the Bi-doped PbTe system. We prove that Bi element is an effective dopant in PbTe responsible for the superior thermoelectric performance. A boosted ZT of ∼1.12 at 673 K and a ZT ave of 0.84 in the range of 300–873 K are achieved for Bi-doped PbTe system.